Integrating In Vitro and In Silico Analysis of a Cationic Antimicrobial Peptide Interaction with Model Membranes of Colistin-Resistant Pseudomonas aeruginosa Strains - Sandra Patricia Rivera-Sanchez; Iván Darío Ocampo-Ibáñez; Yamil Liscano; Natalia Martínez; Isamar Muñoz; Marcela Manrique-Moreno; Luis Martinez-Martinez; José Oñate-Garzon (MDPI AG, 2022)
Bacterial antibiotic resistance is a serious global public health concern. Infections caused by colistin-resistant Pseudomonas aeruginosa (CRPa) strains represent a serious threat due to their considerable morbidity and mortality rates, since most of the current empirical antibiotic therapies are ineffective against these strains. Accordingly, cationic antimicrobial peptides (CAMPs) have emerged as promising alternatives to control resistant bacteria. In this study, the interaction of a CAMP derived from cecropin D-like (∆M2) with model membranes mimicking bacterial biomembranes of wild-type (WTPa) strains of P. aeruginosa and CRPa was evaluated through in vitro and in silico approaches. In vitro interaction was determined by infrared spectroscopy, whereas in silico molecular dynamics was performed to predict specific interactions between amino acids of ∆M2 and lipids of model membrane systems. Experimental analysis showed this peptide interacted with the lipids of bacterial-like model membranes of WTPa and CRPa. In both cases, an increase in the concentration of peptides induced an increase in the phase transition temperature of the lipid systems. On the other hand, the peptides in solution underwent a transition from a random to a helical secondary structure after interacting with the membranes mostly favored in the CRPa system. The α-helix structure percentage for ΔM2 interacting with WTPa and CRPa lipid systems was 6.4 and 33.2%, respectively. Finally, molecular dynamics showed ∆M2 to have the most affinities toward the phospholipids palmitoyl-oleyl-phosphatidylglycerol (POPG) and palmitoyl-oleoyl-phosphatidylethanolamine (POPE) that mimic membranes of WTPa and CRPa, respectively. This work provides clues for elucidating the membrane-associated mechanism of action of ∆M2 against colistin-susceptible and -resistant strains of Pseudomonas aeruginosa.